Early juvenile arthritis – results of two-year follow up - S O Salugina; N N Kuzmina; E S Fedorov; G R Movsisyan (Научно-практическая ревматология)
Objective. To study clinical and laboratory manifestations of different variants of juvenile arthritis (JA) at the disease onset and during prospective two-year follow up. Material and methods. The study was performed as a part of Institute of Rheumatology early arthritis examination program RADIKAL. 130 pts with early JA (60,7% - girls) with disease duration from 2 weeks to 6 months (mean 2,9±1,6 months) aged 1,5- 16 years (mean 7,9±5,0 years) were included. 13 (10%) pts had systemic, 45 (34,6%) – polyarticular and 72 (55,4%) – olygoarticular variant of JA. General state, joint status, systemic and organ manifestation as well as immunological parameters (ANF, RF), disease activity, functional class (by Steinbrocker and CHAQ) were assessed at baseline, and after 6, 12, 24 months of follow up. Results. Oligoarticular variant prevailed at onset and after 2 years (57,6%-55,6%). Systemic features were noted in reduced form as single manifestations. Morning stiffness was absent in half of children and lasted more than 1 hour in 16,4% of pts. After 2 years number of pts with morning stiffness significantly decreased and its duration diminished. Rheumatoid nodules appeared in 1 pt after 1 year. Uveitis developed in 7 children (5,3%) and to the end of follow up it appeared in 2 more pts. Most of pts had minimal or moderate functional disability (FK 1,2 and CHAQ 0,1-1,5) during follow up. Disease activity at onset did not exceed 1 or 2 stage (80,2%) and after 2 years the disease was not active in half of pts. To the end of follow up remission was achieved in 59% of pts, more often in those who received disease modifying anti-rheumatic drugs. In 23,2% of pts mostly in those with polyarthritis JA continued to recur independently on treatment. Conclusion. Timely administered complex therapy hampered disease progression, induced remission and improved quality of life in most children with JA. Pts with olygoarthritis had most favorable course of the disease. Pts with polyarthritis required early administration of aggressive therapy.